The Blended Teaching Practice of College English Audiovisual Courses in Colleges and Universities from the Perspective of BOPPPS Model. (24th September 2022) - Yuan, Minmin
Abstract : In order to solve the practical problems existing in audiovisual teaching, this paper introduces the BOPPPS model and discusses the organizational mode of audiovisual teaching. Firstly, the inherent meaning of BOPPPS model and hybrid teaching is analyzed, and the suitability of BOPPPS model in audiovisual teaching is clarified. Then, the audiovisual teaching framework based on BOPPPS model is constructed from the perspective of practice. Application strategies are summarized from bridge-in, learning objective, preassessment, participatory learning, postassessment, and summary stages and finally explore matters for attention with examples. The process is systematic and comprehensive, which can provide guidance for teaching practice. The results found that after three days of learning with only hearing, 15 percent of students retained their memory, 40 percent of students with only seeing, and 75 percent of students with only hearing. It can break through the time and space limitation of offline classroom teaching and effectively solve the dilemma of audiovisual courses for English majors.